Peran Komunikasi Interpersonal dalam Meningkatkan Kinerja Organisasi Mahasiswa - Faza, Hilwa Faza Nabila Bidawi; Isnaini, Isnaini; Rifai, Ahmad; Manurung, Afwan Syahril (HORIZON: Indonesian Journal of Multidisciplinary, 2025)
Student organizations are an important forum for students to develop themselves and contribute to society. The performance of student organizations is highly dependent on the quality of internal and external communication. Effective interpersonal communication can build strong relationships between members, increase collaboration, and encourage the achievement of organizational goals. This study aims to analyze the role of interpersonal communication in improving the performance of student organizations. This study uses a qualitative approach with a literature study method. Data sources were obtained from various scientific articles and books related to interpersonal communication and student organizations. The source of article data is the database on Google Scholar. Data analysis was carried out descriptively. The results of the analysis show that students' activeness in organizations is positively related to their interpersonal communication skills, which in turn can strengthen social networks and create an inclusive environment. Through organizational experiences, students not only learn to communicate verbally, but also develop the nonverbal and digital skills required in the modern era. Good interpersonal communication can increase student participation in campus activities, strengthen collaboration, and resolve conflicts more effectively